Respuesta :
Answer:
x = 0
Step-by-step explanation:
Divide by -2
-2(x - 2)/-2 = 4/-2
x - 2 = - 2
Add 2 to both sides
x - 2 + 2 = - 2 + 2
x = 0
Answer:
x = 0
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation: -2*(x-2)-(4)=0
This is how your equation should look like (0 - 2 • (x - 2)) - 4 = 0
Solve: -2x = 0
Multiply both sides of the equation by (-1) : 2x = 0
Divide both sides of the equation by 2: x = 0
Please mark as branliest.
Thanks!